Alternative Sources of Financing and Earnings of Startups - Veronika JURICKOVA; Elena GREGOVA (Communications of International Proceedings, 2020)
A startup is a business form that is designed to implement original business ideas that are based on new technologies and the Internet. They represent an attractive alternative for young entrepreneurs compared to traditional employment in a company. They succeeded thanks to the success of companies that were founded at universities or in the garage, and today their founders are the richest people in the world. Technical progress, the opportunities of today's entrepreneurs, and positive examples from the past have influenced the increase in the number of this type of business. Especially in the first stages of a company's life, it is necessary to secure sufficient funds. The main goal of the article is to examine possible alternative possibilities of obtaining financial resources for startups, as well as earnings of startups. Based on this information, it is then possible to determine the advantages or the disadvantage of individual sources of financing, to determine which source of financing is the most used among this type of enterprise. The article uses methods of analysis to obtain the necessary information and methods of comparing the results obtained. The result of the research is a summary and mutual comparison of individual financing options for startups.
Keywords: Startups; Financing; Earnings